Synthesis and Functionalization of Corroles. An Insight on Their Nonlinear Optical Absorption Properties - I.M. Santos, Carla; F.B. Barata, Joana; J.F. Calvete, Mario; S.H.P. Vale, Luís; Dini, Danilo; Meneghetti, Moreno; G.P.M.S. Neves, Maria; A.F. Faustino, Maria; C. Tome, Augusto; A.S. Cavaleiro, Jose (Current Organic Synthesis, 2014)
The development of efficient synthetic methodologies and post-functionalization procedures gave access to a wide variety of new corrole derivatives with potential applications in different areas. This paper reviews the preparation of meso-triaarylcorroles and their functionalization, namely via cycloaddition transformations, and describes the nonlinear optical (NLO) properties of a series of metal-free and gallium corroles with different peripheral substituents. The corroles studied were the free base 5,10,15-tris- (pentafluorophenyl)corrole, the corresponding gallium(III) complex and adducts obtained from 1,3-dipolar cycloaddition reaction. Correlations between the structure and the NLO effect of optical power limiting were attempted in our comparative analysis. The present contribution is one of the first reports on the effect of reverse saturable absorption in the visible spectrum generated by corrole-based complexes.
Keywords: reverse saturable absorption